Cementitious composites containing alum sludge ash: An investigation of microstructural features by an advanced nanoindentation technology. (13th September 2021) - Liu, Yue; Zhuge, Yan; Chow, Christopher W.K.; Keegan, Alexandra; Ma, Jun; Hall, Colin; Li, Danda; Pham, Phuong Ngoc; Huang, Jianyin; Duan, Weiwei; Wang, Lei
Graphical abstract: Highlights: The binder with 10% alum sludge ash exhibits satisfying indentation properties. Alum sludge ash shows lower nanoindentation properties than cement clinker. 30% sludge ash decreased the micromechanical performance of binder paste. The reaction degree of sludge ash may reach 39.0% after curing for 90 days. Concrete blocks with 10% sludge ash exhibit a comparable strength to reference. Abstract: The use of alum sludge ash (ASA) in cement-based composites was investigated in this study, where the cement was replaced by ASA at weight percentages of 0 %, 10 %, 20 %, and 30 %. The results obtained from an advanced nanoindentation technology (coupling conventional statistic nanoindentation and chemical mapping) exhibited that the indentation modulus and hardness of High-density (HD) C-S-H and Low-density (LD) C-S-H as well as the total volumes of C-S-H gel in ASA-incorporated binder pastes were similar. However, the volume fractions of HD C-S-H in the pastes with 10 % ASA were higher than that in 30 % ASA samples. These results might attribute to the fact that the pastes containing 10% ASA exhibited a higher pozzolanic reaction degree, which was determined using the selective dissolution method. The homogenized indentation properties of paste samples with 10 % ASA were also higher than those incorporating 30 % ASA. In addition to considering HD C-S-H gel volume, the increased amount of unreacted ASA with much lower indentation properties than those of cement clinker might result in a deteriorated mechanical performance of binder pastes. In actual engineering practice, the optimum ratio for cement replaced with ASA in concrete was 10 %, which led to a comparable strength to concrete block samples containing 0 % ASA.